How learning theories can be applied to support older adults’ acquisition of digital skills? - Kärnä, Eija; Pihlainen, Kaisa (Magyar Gerontológia, 2020)
Digitalization of public services affects daily life of older adults since adequate digital skills are required in using the digital devices and services. Many organizations have reacted to the growing need of older adults to receive support in using digital services by offering guidance in digital skills. The knowledge of how older adults learn help in successfully organizing digital skills guidance. In this presentation we will introduce the variety of concepts and theories concerning digital skills learning of older adults. We will also share results of peer guidance sessions of older adults from the viewpoints of three different learning theories. Data is collected from eight focus group interviews (N = 42, 62-79 years old). Data was analyzed using theory-driven content analysis. According to the results, peer tutors applied all three learning theoretical approaches in digital skills guidance. Furthermore, peer tutors paid attention to characteristics of ageing that affect learning. At best, peer tutoring sessions were constructed as shared learning practices of both tutors and tutees. Results provide new information about how to support older adults in peer tutoring sessions. Research results can be used in educating peer tutors and teachers of older adults as well as in developing support systems in implementation of digital public services. This research is a part of ACCESS project in which digital skills learning of older adults is investigated in four European countries. The ACCESS project is funded by EU Joint Programming Initiative (JPI) “More Years, Better Lives” The Potential and Challenges of Demographic Change.